Gene Repertoire Evolution of Streptococcus pyogenes Inferred from Phylogenomic Analysis with Streptococcus canis and Streptococcus dysgalactiae - Lefébure, Tristan; Richards, Vince P.; Lang, Ping; Pavinski-Bitar, Paulina; Stanhope, Michael J. (PLOS ONE, 2012)
Streptococcus pyogenes, is an important human pathogen classified within the pyogenic group of streptococci, exclusively adapted to the human host. Our goal was to employ a comparative evolutionary approach to better understand the genomic events concomitant with S. pyogenes human adaptation. As part of ascertaining these events, we sequenced the genome of one of the potential sister species, the agricultural pathogen S. canis, and combined it in a comparative genomics reconciliation analysis with two other closely related species, Streptococcus dysgalactiae and Streptococcus equi, to determine the genes that were gained and lost during S. pyogenes evolution. Genome wide phylogenetic analyses involving 15 Streptococcus species provided convincing support for a clade of S. equi, S. pyogenes, S. dysgalactiae, and S. canis and suggested that the most likely S. pyogenes sister species was S. dysgalactiae. The reconciliation analysis identified 113 genes that were gained on the lineage leading to S. pyogenes. Almost half (46%) of these gained genes were phage associated and 14 showed significant matches to experimentally verified bacteria virulence factors. Subsequent to the origin of S. pyogenes, over half of the phage associated genes were involved in 90 different LGT events, mostly involving different strains of S. pyogenes, but with a high proportion involving the horse specific pathogen S. equi subsp. equi, with the directionality almost exclusively (86%) in the S. pyogenes to S. equi direction. Streptococcus agalactiae appears to have played an important role in the evolution of S. pyogenes with a high proportion of LGTs originating from this species. Overall the analysis suggests that S. pyogenes adaptation to the human host was achieved in part by (i) the integration of new virulence factors (e.g. speB, and the sal locus) and (ii) the construction of new regulation networks (e.g. rgg, and to some extent speB).